Le roman actuel et ses extrapolations : Les Funambules de Mohammed Aïssaoui et Beyrouth-sur-Seine de Sabyl Ghoussoub - Zdrada-Cok, Magdalena (2023)
This article proposes a comparative analysis of two novels: Les Funambules (Gallimard 2020) by Mohammed Aïssaoui and Beyrouth-sur-Seine (Stock, 2022) by Sabyl Ghoussoub. The subject of research is the relationship between novelistic techniques and forms of journalistic discourse. By examining the relationship between the literary text and the socio-cultural context, this study is interested in the presence of various forms of discourse in a literary text, such as the interview, the testimony, the report, the document and the photo.
Keywords: non fiction novel; literature and journalism; autobiography